Thymic Epithelial Cells Contribute to Thymopoiesis and T Cell Development - Wang, Hong-Xia; Pan, Wenrong; Zheng, Lei; Zhong, Xiao-Ping; Tan, Liang; Liang, Zhanfeng; He, Jing; Feng, Pingfeng; Zhao, Yong; Qiu, Yu-Rong (Frontiers in Immunology, 2020)
The thymus is the primary lymphoid organ responsible for the generation and maturation of T cells. Thymic epithelial cells (TECs) account for the majority of thymic stromal components. They are further divided into cortical and medullary TECs based on their localization within the thymus and are involved in positive and negative selection, respectively. Establishment of self-tolerance in the thymus depends on promiscuous gene expression (pGE) of tissue-restricted antigens (TRAs) by TECs. Such pGE is co-controlled by the autoimmune regulator (Aire) and forebrain embryonic zinc fingerlike protein 2 (Fezf2). Over the past two decades, research has found that TECs contribute greatly to thymopoiesis and T cell development. In turn, signals from T cells regulate the differentiation and maturation of TECs. Several signaling pathways essential for the development and maturation of TECs have been discovered. New technology and animal models have provided important observations on TEC differentiation, development, and thymopoiesis. In this review, we will discuss recent advances in classification, development, and maintenance of TECs and mechanisms that control TEC functions during thymic involution and central tolerance.